Enhancing Vocabulary Acquisition for English Language Learners: Innovative Strategies and Practical Approaches - Ameeruddin; Anil S. Apuru (Digital Crossroads: Integrating Humanities, Science and Technology Edition 1, 2025)
The present education system strives to make the students employable and make them successful in getting the right placement. Because of their poor communication skills, they are lagging behind in getting it. It is clear that vocabulary acquisition is a cornerstone of English Language Learning. A rich vocabulary empowers learners to express themselves effectively, comprehend complex texts, and engage in meaningful conversations. Hence vocabulary plays a vital role in effective communication skills. So, this article highlights the easiest way to develop vocabulary. In the present paper, the method will be employed to teach vocabulary to the new entrants during their first academic year. The teachers shed light on the methods that they use to teach the students. For example, if one teacher enters the class and put 2 or 3 words on the board, the teacher will explain the meaning, usage etc., with examples for 4 to 5 minutes. Then they can proceed to their regular lecture. This will be repeated and regular activity by all the teachers when they begin their lectures every day. The present idea will help the students to make a thorough understanding of vocabulary at their present level, equip the students with effective communication skills and make them successful in their lives.